Successful Treatment of a Recalcitrant Staphylococcus epidermidis Prosthetic Knee Infection with Intraoperative Bacteriophage Therapy - James B. Doub; Vincent Y. Ng; Eleanor Wilson; Lorenzo Corsini; Benjamin K. Chan (MDPI AG, 2021)
Here, we present a case of a 79-year-old female with a recalcitrant Staphylococcal epidermidis prosthetic knee infection that was successfully treated with a single dose of adjuvant intra-articular bacteriophage therapy after debridement and implant retention surgery. The bacteriophage used in this case, PM448, is the first ɛ2 bacteriophage to be used in vivo. Currently the patient is without evidence of clinical recurrence and, interestingly, the patient had also suffered from debilitating aplastic anemia for over 2 years, which is recovering since receiving adjuvant bacteriophage therapy.